On the dynamics of the space-charge layer inside the nozzle of a cutting torch and its relation with the "non-destructive" double-arcing phenomenon - Prevosto, L. (2011)
Experimental observations on the plasma dynamics inside the nozzle of a 30 A oxygen cutting torch operated at conditions close to the double arcing are reported. It is employed a technique previously developed in our laboratory consisting in using the nozzle as a large-sized Langmuir probe. Based on the behavior of the ion current signal and simple estimations, it is concluded that (1) the non-equilibrium plasma inside the nozzle is far from the steady state in time, in contrast to what is frequently assumed. The power supply ripple was identified as the main fluctuations source and (2) large-scale plasma fluctuations inside the nozzle could cause transient (total duration of the order of 100 μs) Townsend avalanches developing in the space-charge layer located between the arc plasma and the nozzle wall. Such events trigger the so called non-destructive double-arcing phenomena without appealing to the presence of insulating films deposited inside the nozzle orifice, as was previously proposed in the literature. © 2011 American Institute of Physics.